Heart rate variability as a biobehavioral marker of diverse psychopathologies: A review and argument for an "ideal range". (February 2021) - Heiss, Sydney; Vaschillo, Bronya; Vaschillo, Evgeny G.; Timko, C. Alix; Hormes, Julia M.
Highlights: Heart rate variability (HRV) quantifies the variability in heartbeat intervals. HRV is thought to reflect flexible adaptability to changing environmental demands. Most psychopathologies, except eating disorders, are associated with low HRV. We quantify an "ideal range" of HRV that predicts optimal functioning. This "ideal range" should be targeted in biofeedback interventions. Abstract: Heart rate variability (HRV), a measure of the variability in intervals between subsequent heart beats, is now widely considered an index of emotion regulatory capacity and the ability to adapt flexibly to changing environmental demands. Abnormalities in HRV are implicated in a host of psychopathologies, making it a potentially powerful transdiagnostic biobehavioral change mechanism in treatment interventions. While most mental illnesses are associated with low HRV, eating disorders have been linked to elevated HRV. We examined 62 research articles on HRV in psychopathology to test the hypothesis that there is an "ideal range" of HRV that predicts optimal functioning. Relationships between symptom severity and parameters that quantify HRV were examined graphically. More extreme time-domain HRV measures, both high and low, were associated with psychopathology, whereas healthy controls displayed mid-range values. Findings preliminarily support the hypothesis that there is an "ideal range" of HRV that could be targeted in biofeedback interventions.